ANALYSIS OF SATURATED HYDRAULIC CONDUCTIVITY OF PETUNG BAMBOO (Dendrocalamus asper ) ON SOME TREATMENTS - Veronika Pakpahan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This study aims to determine saturated hydraulic conductivity (Ks) of Petung Bamboo with several treatments.This studywas conducted inMarch-May2015, intheDepartmentofAgriculturalEngineering, FacultyofAgriculture,University of Lampung. The treatments consisted of two factors; firstwas bamboo treatment andthe secondwasbamboo positions. Bamboo treatment consisted of 3 levels; both epidermis and endodermis were not scraped,epidermiswas scraped and endodermiswas not, and both epidermis and endodermiswere scraped. In the secondfactor, bamboo was placed horizontally and vertically. Based on research conducted, Ks of unscraped layers ofthe epidermis and endodermiswas 0 cm.sec-1. For the treatment of scraped epidermis and unscraped endodermis,Kswas 3.04 x 10-10 cm.sec-1. For the treatment of bamboo epidermis and endodermis layers scraped,Kswas 5.40x 10-10 cm.sec-1. Bamboohorizontally placed had higherKs than bamboo vertically placed. The resultalso showedthat bamboowith higher density had lower hydraulic conductivity.Keywords: Hydraulic conductivity, Petung Bamboo